Depth-Dependent Cellular Response from Dental Bulk-Fill Resins in Human Dental Pulp Stem Cells. (24th October 2019) - Lee, Su-Min; Kim, Soo-Youn; Kim, Jae-Heon; Jun, Soo-Kyung; Kim, Hae-Won; Lee, Jung-Hwan; Lee, Hae-Hyoung
Abstract : The proper choice of dental composite resins is necessary based on the minimal cytotoxicity and antiodontogenesis on human dental pulp stem cells for dental pulp-dentin tissue repair and regeneration. The aim of this study was to evaluate the cytotoxicity and antidifferentiation effects of dental bulk-fill resins, able to be polymerized as a bulk status for filling deep cavity of a tooth by single light curing, against human dental pulp stem cells (hDPSCs) from three compartments corresponding to depth (0-2, 2-4, and 4-6 mm) from the light-curing site. Three bulk-fill composite resins (SDR, Venus bulk-fill (VBF), and Beautifil Bulk Flowable (BBF)) and a conventional flowable composite resin (Filtek Z350 XT flowable restorative (ZFF)) were individually filled into a cylindrical hole (h = 2 mm, Ф = 10 mm ), and three compartments (total 6 mm of height) were combined as a single assembly for light curing. The resin samples from the three layers were separated and eluted in the culture medium. The extracts were exposed to hDPSCs, and cytotoxicity and differentiation capability were evaluated. Depth of cure and surface hardness according to depth were determined. All bulk-fill resins except BBF revealed cytotoxicity from 4 to 6 or 2 to 4 mm, while ZFF was cytotoxic at over 2 mm. Depth of cure was detected from 3.55 to 4.02 mm in the bulk-fill resins (vs. 2.25 mm in conventional resin), and 80% hardness compared with that of a fully polymerized top surface was determined from 4.2 to 6 mm in the bulk-fill resin (vs. 2.4 mm in conventional resin). Antidifferentiation was revealed at a depth of 4-6 mm in the bulk-fill resin. There was a difference in depth of cytotoxicity and antidifferentiation between the bulk-fill composite resins, which was mainly due to different cure depths and ingredients. Therefore, careful consideration of choice of bulk-fill resins is necessary especially for restoration of deep cavities for maintaining the viability and differentiation ability of dental pulp stem cells.